Distinct Metabolism of Bone Marrow Adipocytes and their Role in Bone Metastasis - Li, Yixuan; Cao, Shan; Gaculenko, Anastasia; Zhan, Yifan; Bozec, Aline; Chen, Xiaoxiang (Frontiers in Endocrinology, 2022)
Bone marrow adipocytes (BMAs) represent 10% of the total fat mass of the human body and serve as an energy reservoir for the skeletal niche. They function as an endocrine organ by actively secreting fatty acids, cytokines, and adipokines. The volume of BMAs increases along with age, osteoporosis and/or obesity. With the rapid development of multi-omic analysis and the advance in in vivo imaging technology, further distinct characteristics and functions of BMAs have been revealed. There is accumulating evidence that BMAs are metabolically, biologically and functionally unique from white, brown, beige and pink adipocytes. Bone metastatic disease is an uncurable complication in cancer patients, where primary cancer cells spread from their original site into the bone marrow. Recent publications have highlighted those BMAs could also serve as a rich lipid source of fatty acids that can be utilized by the cancer cells during bone metastasis, particularly for breast, prostate, lung, ovarian and pancreatic cancer as well as melanoma. In this review, we summarize the novel progressions in BMAs metabolism, especially with multi-omic analysis and in vivo imaging technology. We also update the metabolic role of BMAs in bone metastasis, and their potential new avenues for diagnosis and therapies against metastatic cancers.
CRIS-Team Scopus Importer:2022-07-22
Keywords: bone marrow adipocytes; bone metastasis; lineage-tracing; metabolism; multi-omic analysis